Bulking coefficients of aerated flow during wave overtopping simulation on protected land-side slopes - Scholl, Bryan N., author; Thornton, Christopher I., advisor; Abt, Steven R., advisor; Hughes, Steven A., committee member; Venayagamoorthy, Subhas K., committee member; Kampf, Stephanie K., committee member (Colorado State University. Libraries, 2016)
Post hurricane Katrina there has been more interest in erosion on the landward side of levees resulting from wave overtopping during storm events. The development of wave overtopping simulators has enabled more rigorous evaluation of levee armoring alternatives under controlled conditions similar to those on levees. Steady state overtopping studies have demonstrated a reduction in shear stress due to air entrainment in the flow. There has not been an evaluation of air entrainment during wave overtopping simulation. For this reason, a study was conducted to quantify flow bulking occurring during wave overtopping simulation. Testing was conducted at the Hydraulics Laboratory at Colorado State University at the Engineering Research Center using a wave overtopping simulator. The simulated levee was 6 ft wide. Levee geometry in the direction of flow was a 13.2 ft. horizontal crest, 30.5 ft levee face with 3:1 (horizontal:vertical) slope and 12.2 ft berm with 25:1 slope. Un-bulked flow thickness was measured with “surfboards” which hydroplane along the surface of flow. Bulked flow thicknesses were measured using visual observations of maximum flow thickness on eight staff gages along the wall of the simulated levee. Wave volumes ranged from 20 ft3/ft to 175 ft3/ft. Conservation of mass and testing repeatability is demonstrated. Bulking values range from zero for the smallest wave volumes to over 100% for the largest wave volumes. An empirical model is developed to estimate bulking on the 3:1 levee slope. A comparison is made to steady state flows with similar air entrainment. The effect of bulking on shear stress is a potential decrease in shear stress over 50% relative to un-bulked flow thickness. A method to incorporate wave overtopping bulking into design is proposed using a cumulative work approach.
Keywords: aeration; levee overtopping; wave overtopping simulation; flow bulking; aerated flow; wave overtopping